Isolated Cranial Nerve VI Palsy in Granulomatosis With Polyangiitis - Alexis Trujillo; David B. Jackson; Jonathon Coy; Chau Tran; Jacob Imber (Annals of Internal Medicine: Clinical Cases)
Granulomatosis with polyangiitis has many presentations and is known to cause optic neuropathies, but the mechanism of injury is usually related to mass effect from a space-occupying granuloma. In this case report, we present a patient with cranial nerve VI mononeuropathy from granulomatosis with polyangiitis secondary to inflammation alone. This underscores the importance of considering vasculitis in the setting of neuropathy even in the absence of space-occupying lesion.